Visualisasi Sebaran Air Tanah Berdasarkan Nilai Resistivitas Dengan Konfigurasi Wenner – Schlumberger Di Desa Air Rami Kabupaten Mukomuko - Sakti, Ridho Eka; Sendiya Verentina; Suhendra; Refrizon; Gayatriani, Intan (Universitas Andalas, 2025)
Research has been conducted on groundwater potential in Air Rami Village, Mukomuko Regency, Bengkulu Province. The research was conducted because Air Rami Village lacks the availability of water from groundwater and often experiences failures in making boreholes, so this research aims to identify and determine the distribution of groundwater in the aquifer layer. In this study using 2D resistivity geoelectric method with wenner-schlumberger configuration that can identify the distribution of groundwater based on resistivity value. Groundwater distribution based on rock resistivity value so that it can be interpreted as an area potentially containing groundwater originating from aquifers. The 2D geoelectric data acquisition used the geoelectric MAE X612 – EM VHR Multi-Channel resistivitymeter with 48 electrodes. Data processing to determine the distribution of groundwater and subsurface rock conditions using Res2Dinv software version 3.71 which produces 2D resistivity cross sections of the earth's subsurface with resistivity values between 3.40 - 21.90 Ω.m. The resistivity value is interpreted as groundwater. Aquifers that store a lot of groundwater are located at positions 240 - 280 m from the starting point of measurement which has a depth of between 20 - 65 m.